THE INVESTIGATION OF THE EFFECT OF DNR-BASED INSTRUCTION ON 8TH GRADE STUDENTS' WAYS OF UNDERSTANDING AND THINKING - Filiz YILDIZ (Fırat University, 2019)
The aim of this research is to examine the effects of DNR-based instruction on 8th Grade Students' ways of understanding and thinking about probability and statistics. For this purpose, the research is designed according to the quasi-experimental design with pre-test-post-test control group. The study group includes 80 eighth grade students studying in a public middle school in Bayrampasa District of Istanbul. There is an experiment (n = 40) and a control group (n = 40) in the study. The normal learning process in the control group continued while DNR-based teaching was carried out in the experimental group. The data in the study which lasted for totally 6.5 weeks (26 hours), were collected through "8th Grade Mathematics Achievement Test’ (8MAT)", ‘The Test of Determining Ways of Understanding and Thinking’ (TDWUT) and activity worksheets. While the quantitative data obtained in the research were analyzed through a statistical program; qualitative data were analyzed descriptively according to ‘Evaluation Form of Ways of Understanding and Thinking’ (EFWUT) which was developed to evaluate students' ways of understanding and thinking about probability and statistics. In the data analysis, the justification schemes used by the students in the problem solving process were coded as external, empirical and analytical according to proof schemes model which was developed by Harel and Sowder (1998). In line with the findings obtained in the research, it is concluded that the students with DNR-based instruction are more effective in developing the ways of understanding and thinking about probability and statistics than the normal teaching process. According to this, it has been determined that students in the experimental group generally had multiple ways of understanding the concepts related to probability and statistics, developed different solution strategies for the problems and used the analytical scheme more than the control group in the process of verifying their answers.